THE ROLE OF ORGANIZATIONAL CULTURE AS A MEDIATING TO INCREASING - Saryadi Saryadi; Indra Hastuti; Novita Dian Setiaji (Journal of Management and Informatics, 2022)
This study is intended to assess the behavior of the variables of motivation, discipline, and leadership on the performance of ASN at the Wonogiri regional Secretariat through organizational culture or without organizational culture.From 140 ASN, be used 114 respondents as sample with Slovin formula were taken with a simple random sampling. The data was then analyzed using a path analysis system and equipped with statistical tests. Field findings show that: 1) Motivation has a significant influence on organizational culture in Wonogiri regional Secretariat; 2) Discipline has a significant influence on the culture of the organization in the Wonogiri regional Secretariat; 3) Leadership has an influence but not significant on the organizational culture in the Wonogiri regional Secretariat; 4) Motivation has a significant effect on the performance of ASN in the Wonogiri regional Secretariat; 5) Discipline has no significant effect on the performance of ASN in the Wonogiri regional Secretariat; 6) Leadership has an influence, although not insignificant, on the performance of ASN in the Wonogiri regional Secretariat; and 7) Organizational culture has a significant influence on the performance of ASN in the Wonogiri regional Secretariat